Psychosocial work factors influencing health, safety, well-being and productivity of waste collectors in developing countries: a scoping review - Samuel Maneen; Nkosi Nkosi Botha; Mustapha Amoadu; Edward Wilson Ansah (BMC Psychology)
Abstract Background Waste collectors play a crucial role in waste management in developing countries, yet little effort has been made to improve their psychosocial health, safety, and well-being. Despite growing research on this group, psychosocial work factors are underexplored, particularly in low-and middle-income countries. This review maps evidence on the psychosocial work factors influencing the health, safety, well-being, and productivity of waste collectors in developing countries. Methods This review followed the guidelines proposed by Arksey and O’Malley, and reported results and findings using PRISMA-ScR. Detailed search was conducted in four main databases: PubMed Central, Ovid, ScienceDirect, and Taylor and Francis, and other online sources. Thorough screening and data extraction were done based on the inclusion criteria to select relevant articles for the review. Thematic analysis and deductive qualitative synthesis were applied in presenting the findings. Thirty-one (31) articles were included in this review. Results The findings revealed that socio-demographic factors such as low socioeconomic status, low education levels, advancing age, and being resident in a rural community significantly influenced psychosocial work stressors among these waste collectors. High job demands, extended working hours, job dissatisfaction, limited job autonomy, and poor work-home balance were identified as other key psychosocial work factors. Workers also faced low social support, workplace violence, discrimination, and organisational challenges such as delayed salaries, lack of training, and ineffective management. These stressors negatively impact workers’ health, contributing to musculoskeletal disorders, infections, vision complications, and high stress levels. Psychosocial work factors further influenced workplace safety, increasing risks of injuries, burnout, and reduced productivity due to absenteeism, presenteeism, and inefficiency. Conclusion The job demands, job insecurity, limited autonomy, inadequate support, and societal stigma faced by waste collectors collectively undermine their occupational and personal well-being. Supportive workplace policies, targeted training programmes, and accessible health services could help mitigate these challenges, creating safer, more productive work environments for waste collectors.